Pembelajaran Efektif Pendidikan Agama Kristen Generasi Milenial - Mariani Harmadi; Agung Jatmiko (Sekolah Tinggi Teologi Baptis Indonesia, 2020)
The portrait of education in Indonesia in the era of the industrial revolution 4.0 demands reforms to usher in the millennial generation which is a demographic bonus entering Indonesia Gold in 2045 so that they become a nation's children who are ready to compete in the era of globalization as well as free humans who are ready to collaborate for the common good. Students as millennial generation grow in an environment with a massive level of information technology system sophistication so that it becomes a challenge for educators who are mostly still migrant-digital, so educators need to develop their competence and professionalism by increasing their ability in the field of computerized technology for the effectiveness of learning for students who are is native-digital. The study of practical theological models on Christian Religious Education is important to base considerations in the selection of effective and relevant learning strategies for students who are both objects and subjects of education in the environment of formal (school), informal (family) and non-formal (religious) institutions as debriefing spirituality and faith.